PENGARUH HARGA, KUALITAS PRODUK, SALURAN DISTRIBUSI, BRAND IMAGE, BRAND TRUST, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KERUPUK RAMBAK LESTARI ECO DESA SEMBUNG TULUNGAGUNG - Agus Setiawan; Rois Arifin; Siti Asiyah (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACT This research was conducted at UD. Lestari Eco the village of Sembung Tulungagung. The purpose of this study was to knowing and analyze the effect of Price, Product Quality, Distribution Channels, Brand Image, Brand Trust and Promotion on Purchasing Decisions Rambak Lestari Eco Crackers the village of Sembung Tulungagung.The variables used are Price, Product Quality, Distribution Channels, Brand Image, Brand Trust and Promotion as independent variables, while the Purchasing Decisions variable is the dependent variable. The sample used in this study was 100 cunsumers at Lestari Eco Tulungagung uses the purposive sampling method. Data collection methods by collecting primary data. The analysis used includes instrument testing, classic assumption tests, normality tests, multiple linear regression, hypothesis testing and coefficient of determination tests using multiple regression analysis using SPSS 17.0 for Windows software.The results showed that the variable Price, Product Quality, Distribution Channels, Brand Image, Brand Trust and Promotion had a simultaneous significant effect on the Purchasing Decision. While partially only Brand Trust and Promotion variables did not have a significant effect. Keywords : Price, Product Quality, Distribution Channels, Brand Image, Brand Trust, Promotion and Purchasing Decision.